The Essesnce of Reality in Dibyendu Palit’s Stories/ গল্পকার দিব্যেন্দু পালিতের বাস্তব-দর্শন (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Life in a megacity is a constant performance. Crowds fill the streets, yet people are islands, drifting through seas of strangers. The rhythm is restlessness: rushing to work, chasing deadlines, navigating traffic, and returning to space that feel less like homes and more like temporary shelters. Time is currency, and no one seems to have enough of it to pause, connect, or even notice. Faces are full of facades and go through a training of corporate smiles, polite nods, but behind this Facades, the realities are raw and unpolished. Anxiety, loneliness and exhaustion simmer beneath the surface. In the inner world of city life, people are striving, sacrificing and often, quietly breaking. Relationships feel transactional. Conversations skim the surface, seldom delving into the depths of fear, dreams and struggles. Urban life thrives on ambition, but it often starves the soul. People become shadows of themselves, walking a tightrope between dreams and survival, with little room for authenticity in the chaos. City glows with glamour and brightness, but inside those lit windows are countless stories of solitude, nakedness and vulnerability. Dibyendu Palit captures those dark stories of city life without any filter. He presents his characters with their raw core of flesh and blood. These unmasked faces often startle us, sometimes leave us amazed. His stories hold up a mirror to our own faces, forcing us to confront ourselves. Dibyendu Palit essentially speaks of the preparatory phase of present dominance of artificial intelligence, highlighting the confusion and helplessness of people entangled in the intricate mechanisms of machines during this period.
Keywords: Dibyendu Palit; story; realistic; mechanism; urban; megacity; darkness; helplessness